Calibrating a HEC-RAS model of V-Notch weir as inline structure using open channel flume flow method and its application for sediment transport - Rabiatul Arbiyah, Ruslan (2015)
The Hydrologic Engineering Center’s River Analysis System (HEC- RAS) is a one-dimensional computer model intended to perform hydraulic calculations for a network of open channels. This model is widely available, free of cost and the most commonly used hydraulic model in the United States. Most HEC-RAS models are steady state. Unsteady flow analysis in HEC-RAS differs in many ways from the traditional steady state analysis. The main objective of this study is to compare the results of the water surface profile between HEC-RAS and the laboratory experiment. The procedure and methodology to collect the data are described. HEC-RAS will determine the water surface profile with three different discharge and manning value. The data is collected along the flume with V-notch weir is placed at fixed point. After the laboratory work is done, the computational work will obtained the result and the comparison is made. HEC-RAS’s result will determine whether it is reliable to use. The prediction of sediment transport in the upstream is determined in this study. From the result and discussion the appropriate manning value is 0.010 s/m1/3 with the value of root mean square error of 0.026358m from the upstream. The sediment transport is occur at the upstream. This research can be conclude that HEC-RAS is reliable to be used